Organized crime and terrorism in the Sahel: Drivers, actors, options - Wolfram Lacher (Stiftung Wissenschaft und Politik (SWP), 2011)
The dimensions of organized criminal activity in the Sahel region have fundamentally changed in recent years. As profits from cocaine smuggling and abductions of foreign nationals increase substantially, criminal networks are expanding their influence, eroding both the rule of law and existing social structures. The growing presence of al Qaeda in the Islamic Maghreb (AQIM) should equally be seen in the context of the developing criminal networks. Attempts to counter this trend by boosting the capacities of regional states in the security sector have failed to address the real problems. The EU and Germany should encourage greater regional cooperation. Key states are Algeria, which claims regional leadership, and Mali, which has yet to begin tackling organized crime
Keywords: 320